2011
DOI: 10.1007/s10562-011-0649-4
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine-Based Chiral Quaternary Alkylammonium Ionic Liquids as Organocatalysts for Asymmetric Michael Additions

Abstract: A series of chiral pyrrolidine-type quaternary alkylammonium ionic liquids were synthesized and served as efficient catalysts for asymmetric Michael additions of aldehydes and ketones to nitroolefins, and the corresponding adducts were obtained in excellent enantioselectivities ([99% ee) and diastereoselectivities ([99% dr) under solvent-free reaction conditions. Furthermore, the catalyst 7c could be recovered for next run of the reaction with similar yield and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…It was reported that acidic additives exhibited important impact on the yield and enantioselectivity of the reaction catalysed by compound 1c. 23 But when 8b was used as a catalyst of the Michael reaction, a similar stereoselectivity to TFA was obtained in the presence of AcOH, CH 3 SO 3 H and p-TsOH (entries 7-9). Also the reaction yield in the presence of CH 3 SO 3 H was lower than that of TFA, AcOH and p-TsOHFinally, it was found that the Michael reaction could proceed without acidic additive to afford similar results (Entry 10).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It was reported that acidic additives exhibited important impact on the yield and enantioselectivity of the reaction catalysed by compound 1c. 23 But when 8b was used as a catalyst of the Michael reaction, a similar stereoselectivity to TFA was obtained in the presence of AcOH, CH 3 SO 3 H and p-TsOH (entries 7-9). Also the reaction yield in the presence of CH 3 SO 3 H was lower than that of TFA, AcOH and p-TsOHFinally, it was found that the Michael reaction could proceed without acidic additive to afford similar results (Entry 10).…”
Section: Resultsmentioning
confidence: 83%
“…General experimental procedure for the Michael addition of cyclohexanone to nitroalkene by chiral catalyst: TFA (2.85 mg 0.025 mmol) was dropped into a solution of the chiral catalyst (0.075 mmol) in cyclohexanone (1g, 10mmol). 23 After stirring for 1 h, nitroalkene (0.5 mmol) was added, and the solution was stirred at r.t. until nitroalkene had disappeared by Analytical TLC (EA: PE = 1:5). The solution was diluted with water (5 mL), and the resulting mixture was extracted with EA (2 mL×3).…”
Section: Preparation Of 8; General Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies related to the synthesis of proline-derived chiral ionic liquids with onium moieties other than imidazolium and their use in asymmetric Michael addition reactions have been published. 1-(Pyrrolidin-2-ylmethyl)pyridinium ionic liquid 44 has been reported by Headley and his co-workers (Scheme 18 ) [ 45 ], and alkyl ammonium ionic liquids bearing N -pyrrolidin-2-ylmethyl group 45 and 46 have been reported by Wang’s group (Scheme 19 ) [ 46 ] and Chen’s group (Scheme 20 ) [ 47 ], respectively.…”
Section: Internal Asymmetric Induction Via Enaminementioning
confidence: 99%
“…Especially, some ionic liquids as simple recyclable chiral catalyst have opened an access for highly enantioselective reactions . Recently, it was reported that the ionic liquid‐supported proline or pyrrolidine derivatives were successfully used in the Michael addition of ketones and aldehydes to nitroolefins, affording the products in high yields and excellent stereoselectivities. These supported catalysts can be recovered by magnetic field or precipitation with diethyl ether.…”
Section: Introductionmentioning
confidence: 99%